MANAJEMEN PASAR UANG ANTAR BANK SYARIAH (PUAS) DI INDONESIA - Yuliani, Ma’rifah; Mawi, Tiarasari (STIE Muhammadiyah Tanjung Redeb, 2017)
, Sharia Interbank Money Market Management (PUAS) in Indonesia. This study aims to determine the management of money market interbank syariah (PUAS) in Indonesia. The results of this study indicate that sharia interbank money market in Indonesia has been recognized by the government with the issuance of Bank Indonesia Regulation on March 31, 2008, Number 10/11 / PBI on Bank Indonesia Sharia Certificates (SBIS). In addition to the above, DSN-MUI has also issued a fatwa on the Interbank Mudharabah Investment Certificate (IMA Certificate) with the following provisions: Interbank investment certificate based on interest, not justified according to sharia; Investment certificates based on a Mudharabah contract called IMA are justified according to sharia; IMA certificates may be transferred only once after first purchase; and IMA certificate transactors are syariah banks as owners of recipients of funds and conventional banks only as owners of funds. The principle that must be held is the mechanism of the financial market must be in accordance with sharia and financial instruments must also be according to sharia, namely the need for trading money market securities based on bai ad-dayn; interbank placements should be made under the Mudharabah scheme; there is an interbank syariah clearing system to be followed by sharia banks and conventional bank sharia branches; and securitization of sharia securities, and then sold as bonds in the secondary market with Mudharabah scheme.